Modern Book Collecting : A Basic Guide to All Aspects of Book Collecting: What to Collect, Who to Buy from, Auctions, Bibliographies, Care, Fakes and Forgeries, Investments, Donations, Definitions, and More - Wilson, Robert A. (EBL-Schweitzer, 2010)
ALSO BY ROBERT A. WILSON; Title Page; Copyright Page; Dedication; Table of Contents; INTRODUCTION; FOREWORD; PREFACE; CHAPTER ONE - WHAT TO COLLECT; CHAPTER TWO - HOW TO BUILD AN AUTHOR COLLECTION; CHAPTER THREE - STARTING WITH AN UNKNOWN AUTHOR; CHAPTER FOUR - IT'S NEVER TOO LATE; CHAPTER FIVE - DEALERS AND COLLECTORS; CHAPTER SIX - BUYING AT AUCTION; CHAPTER SEVEN - OTHER SOURCES; CHAPTER EIGHT - COLLECTOR'S CONDITION; CHAPTER NINE - HOW TO IDENTIFY FIRST EDITIONS; METHODS OF IDENTIFYING FIRST EDITIONS AND FIRST PRINTINGS OF BOOKS ISSUED BY IMPORTANT BRITISH AND AMERICAN PUBLISHING FIRMS